Answer:
1. The zeros are x = -5 & 3
2. The zeros are x = -4 & 9
3. Zero = x = 7
Explanation:
Whenever we have an expression in the form:
Where a and b are constants
To find zeros, we take each term and equate to zero. That would be:
x - a = 0
x = a
and
x - b = 0
x = b
Likewise, let's find the zeros of each of the functions given:
1.
So,
x - 3 = 0
x = 3
and
x + 5 = 0
x = -5
The zeros are x = -5 & 3
2.
So,
x - 9 = 0
x = 9
and
x + 4 = 0
x = -4
The zeros are x = -4 & 9
3.
x - 7 = 0
x = 7
The zero of this function is x = 7